แนวโน้มความภักดีของผู้บริโภคในอำเภอเมืองเชียงใหม่ต่อตราสินค้ารถยนต์ - ศิวลี อินทรวัตร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This independent study aimed to investigate loyalty tendency of consumers in Mueang Chiang Mai district towards automobile brands. Population of this study included automobile owners who planned to purchase a new automobile within the next year. Data collection was completed by questionnaires and data obtained were assessed by the descriptive statistics, comprising of frequency, percentage, and mean. The findings presented that most respondents were male in the age of 40-49 years old with bachelor’s degree. They worked as government/state enterprise officers and had 3-4 family members. Their monthly income was ranged at 15,001-30,000 Baht and their family owned the total number of 1-2 automobiles. They currently used Toyota brand for their personal automobile (sedan). Within the next year, they planned to purchase the new personal automobile (sedan) in the same brand. Results of the study on loyalty tendency of consumers in Mueang Chiang Mai district towards automobile brands were showed as follows. The respondents rated on the behavior of brand switching cost at strongly agree level; but on the behaviors of loyalty to none of brand and purchasing a product with familiarity at agree level. They, however, rated on the behaviors of being friend and committing to a certain brand at neutral level.